Pemodelan protein dan analisis molecular docking enzim β-glukanase solat Bacillus subtilis W3.15: - Ainia Hanifitri; Laksmi Ambarsari; Nisa Rachmania Mubarik (Menara Perkebunan, 2023)
The β-glucanase enzyme is an enzyme protein that can hydrolyze β-glucan, one of the main components of the fungal cell wall. This enzyme protein is produced by several bacteria, one of which is B. subtilis. The three-dimensional (3D) structure of proteins is necessary to understand their properties and functions of proteins. Enzyme proteins can be analyzed for their structure and function using in silico method. This study aims to detect the β-glucanase gene from B. subtilis W3.15 and analyze it using the in silico method. The methods in this research are homology modeling and molecular docking analyses. Modeling was carried out using the SWISS-MODEL server and docking analysis using the PLANTS 1.1 program. Modeling the β-glucanase enzyme is based on the template of the β-glucanase enzyme protein model with PDB code 3o5s. The results of sequence alignment and model visualization were quite good as indicated by the model having a Ramachandran Plot value in the favored area of 91.10 %, a MolProbity score of 0.95, and a QMEAN value of 0.90 ± 0.06. The β-glucanase enzyme model was then docked using the PLANTS1.1 program with native ligand B3P, 1,4-β-D-Glucan, D-glucose, β-D-Glucan from oats, and N-Acetyl glucosamine. The results of docking analysis showed that the β-glucan ligand (β-D-glucan from oats) used as a substrate in the cultivation of isolate B. subtilis W3.15 had a better binding energy prediction value compared to the B3P ligand, which is a natural ligand in the template proteins.   [Keywords: β-Glucan, β-D-Glucan from oat, ligand, PLANTS 1.1, 3D structure, SWISS-MODEL]